Assessment of Indoor Air Quality in Primary School Classrooms: A Case Study in Mbuji Mayi and Lubumbashi, Democratic Republic of Congo - Jean Paul Kapuya Bulaba Nyembwe; Junior Florent Mbwisi Takizala; Serge Kalonji Muangala; Olivier Kayembe Nyembwe; John Omomoluwa Ogundiran; Manuel Gameiro da Silva (Buildings)
This study assesses indoor air quality (IAQ) in two schools in the Democratic Republic of Congo (DRC), contributing scientific data for a developing tropic such as the DRC marked by the absence of sufficient study on the indoor environmental quality (IEQ) in school buildings. Over ten weeks, we monitored IEQ parameters in two schools, considering their unique geographical and environmental settings. Using a calibrated IEQ multiprobe and particle counters, we measured the CO2 levels, temperature, relative humidity, and particulate matter (PM). Our data analysis, which included ANOVA and correlation assessments, revealed a concerning trend. We found that the CO2 and PM concentrations in the classroom were significantly high, often exceeding recommended safety thresholds. The current natural ventilation systems were found to be inadequate, particularly in managing CO2 concentrations and PM levels influenced by proximity to industrial activities. Our study recommends that schools in similar settings adopt mechanical ventilation systems with high-efficiency particulate air (HEPA) filters to improve IAQ. We also recommend regular monitoring and dynamic air quality adjustment based on real-time data to ensure the effectiveness of implemented interventions. Furthermore, we propose that future studies focus on a broader range of environmental conditions and include many schools and educational buildings to enhance the generalisability of the findings. Long-term health outcomes and the cost-effectiveness of different ventilation strategies should also be explored to develop adapted, sustainable interventions for improving student well-being and performance in schools globally.